ASSESSMENT OF INTERFEROMETRIC DEMS FROM TERRASAR-X STRIPMAP AND SPOTLIGHT STEREOPAIRS: CASE STUDY IN ISTANBUL - Sefercik, Umut G.; Yastikli, Naci (WILEY, 2014)
TerraSAR-X (TSX) has led to a new era for synthetic aperture radar (SAR) imaging, offering high-resolution (1 m) data that was not previously available from space. The TSX X-band sensor can be operated in three interferometrically compatible imaging modes: Stripmap (SM), high-resolution Spotlight (HS) and ScanSAR. Due to the low resolution of ScanSAR (16 to 30 m), SM and HS images are preferred for resolution-based applications. This paper attempts to validate and compare the digital elevation models (DEMs) derived from TSX SM and HS image pairs. Digital surface models (DSMs) were generated by interferometry in a part of Istanbul with a variety of ground types. These DSMs were converted to DEMs by filtering and then compared with a reference DEM produced from aerial photographs. The quality assessment was performed using advanced analyses concerned with accuracy and morphologic detail. The results of both absolute and relative accuracy analyses clearly reveal that the quality of the TSX HS DEM is better than SM and very consistent with the reference model.
Keywords: accuracy assessment; DEM; high-resolution Spotlight; interferometric synthetic aperture radar (InSAR); Stripmap; TerraSAR-X (TSX); CALIBRATION; Physical Geography; Geology; Remote Sensing; Imaging Science & Photographic Technology